(untitled) (Global Journal of Human-Social Science, 2024)
The article discusses the problems of creating innovative educational methods that include reflective technologies. The emphasis is placed on a detailed analysis of theoretical and practical works related to the analysis of reflection in psychological science, which became the basis for the formation of a method of learning through reflective dialogue. The study sets out in detail the criteria necessary for conducting a reflective dialogue, defines its structural elements and fundamental principles. The author’s program of developing classes based on the educational reflexive dialogue «Personality Life Project» is presented, aimed at developing a personal project through a series of educational sessions based on reflexive dialogue. The article describes the methodology and results concerning the impact of reflexive learning dialogue on the development and transformation of life projects in adolescents. Based on the experimental data obtained, the author shows that the technology, which includes a learning reflective dialogue, has a stable positive effect on students’ understanding and rethinking of life orientations, regardless of their individual characteristics.